WT1 directs normal progesterone receptor–chromatin binding essential for uterine receptivity at peri-implantation - Zhangli Ni; Chuanhui Guo; Xiaojing Liu; Gaizhen Li; Yedong Tang; Han Cai; Weiyu Huang; Fei Gao; Zhaowei Tu; Chao Wang; Haibin Wang; Shuangbo Kong; et al. (Proceedings of the National Academy of Sciences, 2025)
Progesterone receptor (PR)-mediated progesterone (P4) signaling plays a crucial role in the establishment of uterine receptivity which is the prerequisite for successful embryo implantation in mammals. However, detailed molecular mechanisms underlying PR–chromatin binding and transcriptional activity in the uterus remain largely elusive. Here, combining the P4-administrated ovariectomized mouse model and PR–chromatin immunoprecipitation sequencing, we identified transcription factor WT1 as a potential cooperator of PR in the uterus. WT1 was specifically expressed in uterine stromal cells. Uterine deletion of Wt1 resulted in implantation failure due to attenuated P4 responsiveness in stromal cells and aberrant uterine receptivity. Mechanistically, WT1 physically interacted with PR in stromal cells, and exhibited genome-wide co-occupancy with PR. Furthermore, WT1 was indispensable for directing PR onto the chromatin via corecruitment and tethering manners, and facilitated PR to activate the transcription of target genes that were critical for uterine receptivity. Collectively, our study provided substantial evidence that WT1 served as a functional partner of PR in uterine stromal cells, thus guaranteeing P4 responsiveness conducive to uterine receptivity.